18-6a=4a+4(a+3)

Simple and best practice solution for 18-6a=4a+4(a+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 18-6a=4a+4(a+3) equation:



18-6a=4a+4(a+3)
We move all terms to the left:
18-6a-(4a+4(a+3))=0
We calculate terms in parentheses: -(4a+4(a+3)), so:
4a+4(a+3)
We multiply parentheses
4a+4a+12
We add all the numbers together, and all the variables
8a+12
Back to the equation:
-(8a+12)
We get rid of parentheses
-6a-8a-12+18=0
We add all the numbers together, and all the variables
-14a+6=0
We move all terms containing a to the left, all other terms to the right
-14a=-6
a=-6/-14
a=3/7

See similar equations:

| 1/7x28=x | | 3n^2+21n+18=0 | | -7/8+p=1/4 | | 5b+3b=-40 | | 2(8-4x)=1/3(33-18x)=3 | | 63+32+h=108 | | 11-(-2-4y=2(y+2) | | (4x+140)+80=180 | | 5x^2-7=48 | | 2x^2+3-5=-2 | | 11-(-2-4y=2(y+2)= | | -20=-5/6v | | 1/2(4x-8)=8;-2 | | |2x-19|=4x-1 | | (7-4i)/(9+2i)=0 | | S+0.06s=1.06s | | x-7/5=5/6 | | 72+g=180 | | 17a+18a+18=-17 | | 8x+-3+-4x=-9 | | -2m+5+7m=13+5(m+1) | | -2(4-3x)+3x=27+2x | | 0.5+0.3(h-6)=0.83h+2 | | 14+4n=5n-6 | | X+4=x+7 | | x/8+6=-12;-48 | | 1/2(y-36)=12 | | 7(1-3)+n=6-(n-4) | | -34+6x=3x+44 | | 15=d-5 | | 6+2(3y-5)=6+3y-5 | | 14.45+0.08x(x=3)=14.95+0.11 |

Equations solver categories